Avaliação da eficácia da administração tópica de lipossomas contendo alumínio-cloro-ftalocianina combinada à terapia sistêmica para tratamento da leishmaniose cutânea experimental. - Raphaela Ariany dos Santos Silva (2021)
After several decades of studies on leishmaniasis, there is still no really effective and non-toxic treatment for the different clinical forms of this parasitosis. Pentavalent antimonial compounds are used as the first choice for the treatment of leishmaniasis, including cutaneous leishmaniasis (CL), however, they have factors that limit their use, such as high toxicity, low adherence and the route of parenteral administration. The development of alternative therapies, including the identification of effective drugs for the topical and/or oral treatment of CL, is desirable. In this context, topical photodynamic therapy (PDT) associated with systemic treatment is an interesting alternative. PDT is based on the activation of a photosensitizing molecule, such as chloro-aluminum-phthalocyanine (AlClFc), which produces reactive oxygen species that induce the destruction of the parasite. As an alternative to oral treatment, Fexinidazole (Fex), a nitroimidazole, has also been researched for the treatment of CL. However, both AlClFc and Fex have limitations, including low water solubility. Thus, this work proposes to prepare liposome containing AlClFc (Lip-AlClFc) and selfemulsifying drug delivery systems containing Fex (SEDDS-Fex), to characterize chemically and physicochemically these systems regarding size, polydispersion index, zeta potential, content and concentration; and evaluate the efficacy in the treatment of CL in animals infected with L. (L.) amazonensis or L. (L.) major. Two batches of each of the formulations were prepared: Lip-AlClFc 1, and 2 and SEDDS-Fex 1 and 2. As the formulations presented adequate characteristics for the proposed routes of administration, efficacy studies were carried. BALB/c mice were infected with L. (L.) amazonensis, separated into groups and treated with: Lip-AlClFc, SEDDS-Fex, Glucantime®, Lip-AlClFc+SEDDS-Fex combination, Lip-AlClFc+Glucantime® combination and control (no treatment). The results showed that there was stabilization in the size of the lesions of animals treated with the combinations of LipAlClFc+Glucantime® and Lip-AlClFc+SEDDS-Fex, without a significant reduction in the parasite load on the lesion. However, the combination Lip-AlClFc+SEDDS-Fex was able to reduce the parasite load in the spleen. Animals infected with L. (L.) major were treated with: Lip-AlClFc, SEDDS-Fex, Lip-AlClFc+SEDDS-Fex combination, suspension-Fex and control (no treatment). The results showed that there was a reduction in the size of the lesions in animals treated with the combination of LipAlClFc+SEDDS-Fex, with significant reduction in the parasite load in the lesion andspleen. Thus, the results obtained in this work indicate that the Lip-AlClFc+SEDDSFex combination may be promising for the treatment of CL caused by L. (L.) amazonensis or L. (L.) major.